Lithium battery thickened positive plate preparation method based on softening purpose

CN119581494APending Publication Date: 2025-03-07NINGBO GP ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411771318.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

Smart Images

  • Figure CN119581494A_ABST
    Figure CN119581494A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery thickened positive plate preparation method based on a softening purpose, which comprises the following steps: S1, uniformly mixing water and N-methyl pyrrolidone, then adding a binder, and further uniformly stirring to form a solution system; s2, fully and uniformly mixing a positive electrode active material and conductive carbon to form modified powder; s3, adding the modified powder into the solution system, and uniformly stirring to prepare positive aqueous slurry; s4, coating a current collector with the positive aqueous slurry, and performing high-temperature drying, calendering and slitting to form a prefabricated positive plate; t1, performing secondary high-temperature heating on the prefabricated positive plate to remove moisture; and (T2) applying a softening organic solvent to the prefabricated positive plate dried in the step (T1) in a liquid spraying manner or a steam infiltration manner to form the lithium battery positive plate for winding based on the softening purpose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a thickened positive electrode sheet of a lithium battery for the purpose of increasing flexibility. Background Art

[0002] With the rapid development of the lithium battery industry and the rapid expansion of production capacity, lithium battery factories are paying more and more attention to the improvement of production efficiency and production quality. Lithium-ion batteries have the advantages of high cycle performance, high operating voltage and low pollution, and lithium primary batteries have the characteristics of long life and high safety, so they are widely used in various electronic devices. In recent years, with the continuous development of science and technology, the functions of electronic equipment have been continuously upgraded, and higher requirements have been put forward for the energy and rate performance of lithium batteries. One of the key technologies of high-energy lithium-ion batteries is the research and development of high-performance positive electrode materials. The performance of positive electrode materials greatly affects the electrical properties and production and processing performance of lithium-ion batteries, and directly determines the cost of batteries.

[0003] CN118589057A patent discloses a method for preparing a high energy density lithium iron phosphate battery, comprising the following steps:

[0004] Step 1: Mix lithium iron phosphate, lithium supplement agent, flexibilizer, graphene composite conductive slurry and polyvinylidene fluoride in a certain mass ratio, then add N-methylpyrrolidone, stir in a vacuum mixer to obtain positive electrode slurry; Step 2: Apply the positive electrode slurry on the positive electrode current collector aluminum foil, first bake it in an oven, and then cold press, cut and slice it to obtain a positive electrode sheet.

[0005] In the field of lithium batteries, the positive electrode is generally coated with a thin thickness. After the electrode is dried, it will not crack, and it will not break when winding. However, due to process requirements, the thickness of the positive electrode coating is thickened, which increases the cracking phenomenon when the electrode is dried. At the same time, during the drying process before winding, due to the volatilization of small molecules such as water and adhesive dispersion, gaps appear inside the electrode, causing the electrode to crack and break when winding, thus limiting the increase in the thickness of the positive electrode coating.

[0006] The main reason for the cracking of the electrode is the capillary force generated during the drying process. When the wet coating dries, the curved liquid surface of the air-solvent interface between the particles generates capillary force. As the solvent evaporates, the capillary force increases, exerting further compression on the particles, and eventually causing the coating to crack. In addition, the formation of voids inside the positive electrode after drying also increases the fragility of the electrode, making it easy to break during processing.

[0007] CN117954571A patent discloses a method for solving the cracking of positive electrode coating of lithium battery, which includes the following steps: S1: pre-treating the positive electrode active material to obtain active powder with particle size of D90≤3.0μm, D99≤6.0μm, D50 between 0.6 and 1.0μm, and active powder with pH≤8.8; S2: mixing the active powder, conductive agent, binder and solvent to prepare positive electrode slurry; S3: coating the positive electrode slurry on the current collector, drying, and obtaining a crack-free positive electrode sheet. The present invention pre-treats the positive electrode active material so that the particle size and proportion of the secondary agglomerated large particles are reduced; increasing small particles can significantly improve the cracking of coating; at the same time, by increasing the nitrogen flow rate of the kiln and increasing the power of the air flow mill, the pH of the positive electrode active material is reduced, the damage of the CF bond of PVDF by residual alkali is reduced, and the microgel is reduced, thereby improving the cohesion of the material particles.

[0008] However, this method requires pretreatment of the powder, which has secondary problems such as complex process, poor operability, and serious pollution of the working environment, and may also introduce impurities that affect subsequent battery performance. Therefore, relevant industry researchers need to further innovate and improve the preparation process to seek a more convenient and safe process to improve the flexibility of the positive electrode sheet and avoid brittle cracking. Summary of the invention

[0009] Based on the shortcomings of the prior art, the present invention provides a method for preparing a positive electrode sheet for a lithium battery with a simpler process and better operability for the purpose of increasing the flexibility of the positive electrode sheet.

[0010] The technical solution provided by the present invention to solve the above technical problems is: a method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility, comprising a step of prefabricating a positive electrode sheet and a step of preparing a winding electrode sheet;

[0011] The steps of prefabricating the positive electrode sheet include:

[0012] Step S1: mixing water and N-methylpyrrolidone uniformly, then adding a binder and further stirring to form a solution system;

[0013] Step S2: fully and evenly mix the positive electrode active material and the conductive carbon to form a modified powder;

[0014] Step S3: adding the modified powder into the solution system, stirring evenly, and making a positive electrode aqueous slurry.

[0015] Step S4: coating the positive electrode aqueous slurry on the current collector, and forming a prefabricated positive electrode sheet after high-temperature drying, calendering and slitting.

[0016] The steps for preparing the pole piece for winding include:

[0017] Step T1: The prefabricated positive electrode sheet is heated at high temperature for a second time to remove moisture;

[0018] Step T2: applying a softening organic solvent to the prefabricated positive electrode sheet dried in step T1 by liquid spraying or steam infiltration to form a lithium battery positive electrode sheet for the purpose of softening for winding.

[0019] The preferred technical solution provided by the present invention to solve the above technical problem is: when N-methylpyrrolidone and water are mixed in step S1, the weight proportion of N-methylpyrrolidone is 2-50%.

[0020] The preferred technical solution provided by the present invention to solve the above technical problem is: the binder used in step S1 includes one or a combination of two of polyacrylic acid dispersion, polyacrylonitrile dispersion, polytetrafluoroethylene emulsion, and sodium carboxymethyl cellulose aqueous solution.

[0021] The preferred technical solution provided by the present invention to solve the above technical problem is: the conductive carbon used in step S2 includes one or a combination of two of graphite, carbon black, carbon nanotubes, vapor-grown carbon fibers, graphene, and graphite fluoride.

[0022] The preferred technical solution provided by the present invention to solve the above technical problem is: in step S4, the positive electrode aqueous slurry is coated on the current collector by transfer or spraying.

[0023] The preferred technical solution provided by the present invention to solve the above technical problem is: in step S2, the positive electrode active material includes any one of manganese dioxide, iron disulfide, carbon fluoride, lithium manganate, lithium cobaltate, lithium nickel cobalt manganate, and lithium iron phosphate.

[0024] The preferred technical solution provided by the present invention to solve the above technical problem is: in step S4, the current collector is copper foil, or aluminum foil, or stainless steel foil.

[0025] The preferred technical solution provided by the present invention to solve the above technical problems is: the softening organic solvent in step T2 includes any one of propylene carbonate, ethylene carbonate, hexanediol dimethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and propylene carbonate.

[0026] The preferred technical solution provided by the present invention to solve the above technical problems is: in step S4, the positive electrode aqueous slurry is coated on the current collector, and the thickness of the positive electrode sheet after coating on both sides is 0.50-1.0 mm (including foil), and the positive electrode sheet formed in step T2 for the purpose of flexibility is formed by rolling the positive electrode sheet in step S4, and the thickness of the positive electrode sheet on both sides after rolling is 0.25-0.50 mm (including foil).

[0027] The preferred technical solution provided by the present invention to solve the above technical problem is: the weight ratio of the softening organic solvent in step T2 to the prefabricated positive electrode sheet prepared in step T1 is 0.2-10.0%.

[0028] Compared with the prior art, the advantages of the present invention mainly include:

[0029] First, the flexibility of the electrode is increased by subsequent treatment with a softening organic solvent. Compared with the prior art method of pre-treating the powder particle size, the process is simpler and more operable.

[0030] Second, by precisely filling the softening organic solvent molecules, it not only effectively fills up the tiny gaps left by small molecules such as water, N-methylpyrrolidone (NMP) and binder dispersion after volatilization, but also plays a bridge-like connecting role, significantly enhancing the flexibility and structural stability of thicker positive electrode sheets during the winding process. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and preferred embodiments, but those skilled in the art will appreciate that these drawings are drawn only for the purpose of explaining the preferred embodiments and therefore should not be used as a limitation on the scope of the present invention. In addition, unless otherwise specified, the drawings are only schematically representing the composition or structure of the described objects and may contain exaggerated displays, and the drawings are not necessarily drawn to scale.

[0032] Figure 1 : The prefabricated positive electrode sheet in the comparative example after drying at 90°C and 80°C was severely cracked;

[0033] Figure 2 : The prefabricated positive electrode sheet after drying at 90° C. in Example 1 was slightly cracked;

[0034] Figure 3 : The prefabricated positive electrode sheet after drying at 80°C and 70°C in Example 1 does not crack;

[0035] Figure 4 :The positive electrode sheet of the lithium battery used for winding cracks during winding;

[0036] Figure 5 :The positive electrode sheet of the lithium battery used for winding maintains structural integrity during winding. DETAILED DESCRIPTION

[0037] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It will be appreciated by those skilled in the art that these descriptions are only illustrative and exemplary and should not be construed as limiting the scope of protection of the present invention.

[0038] It should be noted that like reference numerals denote similar items in the following drawings, and thus, once an item is defined in one drawing, it may not be further defined or explained in subsequent drawings.

[0039] Embodiment 1:

[0040] The present embodiment provides a method for preparing a positive electrode sheet for winding of a lithium battery for the purpose of increasing flexibility, including a step of prefabricating a positive electrode sheet and a step of preparing a winding electrode sheet.

[0041] The steps of prefabricating the positive electrode sheet include:

[0042] Step S1: Mix water and N-methylpyrrolidone in a ratio of 98:2, add a binder after completely releasing heat, and stir evenly to form a stable solution system. The addition of N-methylpyrrolidone reduces the surface tension of the main component water, thereby reducing the possibility of subsequent cracking of the positive electrode sheet.

[0043] In this embodiment, the binder is polyacrylic acid dispersion, which can be one or a combination of polyacrylic acid dispersion, polyacrylonitrile dispersion, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose aqueous solution.

[0044] Step S2: Fully and uniformly mix the positive electrode active material and the conductive carbon, so that the surface of the positive electrode active material is coated with the conductive carbon to achieve the material modification effect and form a modified powder.

[0045] In this embodiment, the conductive carbon is a mixture of carbon black and graphite. The positive electrode active material is manganese dioxide. Of course, the positive electrode active material can also be any one of iron disulfide, carbon fluoride, lithium manganate, lithium cobaltate, lithium nickel cobalt manganate, and lithium iron phosphate. The conductive carbon used includes one or a combination of two of graphite, carbon black, carbon nanotubes, vapor-grown carbon fibers, graphene, and graphite fluoride.

[0046] Step S3: adding the modified powder into the solution system, stirring evenly, and making a positive electrode aqueous slurry.

[0047] Step S4: Coat the positive electrode aqueous slurry on both sides of the current collector with a coating thickness of 0.68-0.71mm. After high-temperature drying, calendering and slitting, the prefabricated positive electrode sheets are formed. The drying temperatures are 90℃, 80℃ and 70℃ respectively. The calendering thickness is 0.43-0.46mm. As shown in the figure, slight cracking occurs when dried at 90℃. As shown in the figure, no cracking occurs when dried at 80℃ and 70℃.

[0048] Usually, the positive electrode aqueous slurry is coated on the current collector by transfer or spraying, and the current collector is copper foil, aluminum foil, or stainless steel foil. In this embodiment, the current collector is copper foil, and the positive electrode aqueous slurry is coated on it by spraying.

[0049] It should be noted that the calendering process greatly reduces the thickness of the positive electrode sheet, or even reduces it by half. That is, in step S4, the positive electrode aqueous slurry is coated on the current collector, and the thickness of the positive electrode sheet after coating on both sides can be preferably 0.50-1.0 mm (including foil), and the positive electrode sheet formed in step T2 for the purpose of flexibility is formed by rolling the positive electrode sheet in step S4, and the thickness of the positive electrode sheet on both sides after rolling is 0.25-0.50 mm (including foil).

[0050] The steps for preparing the pole piece for winding include:

[0051] Step T1: The prefabricated positive electrode sheet treated at a drying temperature of 80° C. in step S4 is heated at the same temperature for a second time to remove moisture.

[0052] Step T2: Propylene carbonate is heated as a softening organic solvent to form steam, and is applied to the prefabricated positive electrode sheet dried in step T1 through steam infiltration to form a lithium battery positive electrode sheet for winding for the purpose of softening. Steam infiltration occurs based on the interaction force between steam molecules and the solid surface. When steam molecules contact the solid surface, they are affected by the attraction of the solid surface and adhere to the solid surface. As the number of steam molecules continues to increase, they will gradually penetrate into the solid, forming a steam infiltration phenomenon. Therefore, the organic solvent can occupy the voids left by the water molecules lost in step S4 and step T1, thereby achieving the purpose of softening. By controlling the concentration of the softening organic solvent atmosphere and the processing time, the mass proportion of the softening organic solvent in step T2 relative to the prefabricated positive electrode sheet prepared in step T1 is controlled to be 0.2-10.0%.

[0053] In other embodiments, the softening organic solvent may be any one of ethylene carbonate, hexanediol dimethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and propylene carbonate. The softening organic solvent may also be applied to the prefabricated positive electrode sheet dried in step T1 by liquid spraying.

[0054] Embodiment 2:

[0055] The present embodiment provides a method for preparing a positive electrode sheet for winding of a lithium battery for the purpose of increasing flexibility, including a step of prefabricating a positive electrode sheet and a step of preparing a winding electrode sheet.

[0056] The steps of prefabricating the positive electrode sheet include:

[0057] Step S1: Mix water and N-methylpyrrolidone in a ratio of 90:10, then add a binder, stir evenly, release heat, and form a stable solution system. The addition of N-methylpyrrolidone reduces the surface tension of the main component water, thereby reducing the possibility of subsequent cracking of the positive electrode sheet.

[0058] In this embodiment, the binder is a polyacrylic acid dispersion.

[0059] Step S2: Fully and uniformly mix the positive electrode active material and the conductive carbon, so that the surface of the positive electrode active material is coated with the conductive carbon to achieve the material modification effect and form a modified powder.

[0060] In this embodiment, the conductive carbon is a mixture of carbon black and graphite, and the positive electrode active material is manganese dioxide.

[0061] Step S3: adding the modified powder into the solution system, stirring evenly, and making a positive electrode aqueous slurry.

[0062] Step S4: Coat the positive electrode aqueous slurry on both sides of the current collector with a coating thickness of 0.68-0.71 mm. After high-temperature drying, rolling and slitting, the prefabricated positive electrode sheets are formed. The drying temperatures are 90°C, 80°C and 70°C respectively. The rolling thickness is 0.43-0.46 mm. Different from the first embodiment, the prefabricated positive electrode sheets at the three drying temperatures in this embodiment did not crack.

[0063] The steps for preparing the pole piece for winding include:

[0064] Step T1: The prefabricated positive electrode sheet treated at a drying temperature of 80° C. in step S4 is heated at the same temperature for a second time to remove moisture.

[0065] Step T2: Propylene carbonate is heated as a softening organic solvent to form steam, and is applied to the prefabricated positive electrode sheet dried in step T1 by steam infiltration to form a lithium battery positive electrode sheet for winding for the purpose of softening. By controlling the concentration of the softening organic solvent atmosphere and the treatment time, the weight ratio of the softening organic solvent in step T2 to the prefabricated positive electrode sheet prepared in step T1 is controlled to be 0.2-10.0%.

[0066] Embodiment three:

[0067] The present embodiment provides a method for preparing a positive electrode sheet for winding of a lithium battery for the purpose of increasing flexibility, including a step of prefabricating a positive electrode sheet and a step of preparing a winding electrode sheet.

[0068] The steps of prefabricating the positive electrode sheet include:

[0069] Step S1: Mix water and N-methylpyrrolidone in a ratio of 50:50, then add a binder, stir evenly, release heat, and form a stable solution system. The addition of N-methylpyrrolidone reduces the surface tension of the main component water, thereby reducing the possibility of subsequent cracking of the positive electrode sheet.

[0070] In this embodiment, the binder is a polyacrylic acid dispersion.

[0071] Step S2: Fully and uniformly mix the positive electrode active material and the conductive carbon, so that the surface of the positive electrode active material is coated with the conductive carbon to achieve the material modification effect and form a modified powder.

[0072] In this embodiment, the conductive carbon is a mixture of carbon black and graphite, and the positive electrode active material is manganese dioxide.

[0073] Step S3: adding the modified powder into the solution system, stirring evenly, and making a positive electrode aqueous slurry.

[0074] Step S4: Coat the positive electrode aqueous slurry on both sides of the current collector with a coating thickness of 0.68-0.71 mm. After high-temperature drying, rolling and slitting, the prefabricated positive electrode sheets are formed. The drying temperatures are 90°C, 80°C and 70°C respectively. The rolling thickness is 0.43-0.46 mm. Different from the first embodiment, the prefabricated positive electrode sheets at the three drying temperatures in this embodiment did not crack.

[0075] The steps for preparing the pole piece for winding include:

[0076] Step T1: The prefabricated positive electrode sheet treated at a drying temperature of 80° C. in step S4 is heated at the same temperature for a second time to remove moisture.

[0077] Step T2: Propylene carbonate is heated as a softening organic solvent to form steam, and is applied to the prefabricated positive electrode sheet dried in step T1 by steam infiltration to form a lithium battery positive electrode sheet for winding for the purpose of softening. By controlling the concentration of the softening organic solvent atmosphere and the treatment time, the weight ratio of the softening organic solvent in step T2 to the prefabricated positive electrode sheet prepared in step T1 is controlled to be 0.2-10.0%.

[0078] Comparative Example:

[0079] This comparative example provides a method for preparing a positive electrode sheet for winding of a lithium battery, comprising a step of prefabricating a positive electrode sheet and a step of preparing a winding electrode sheet.

[0080] The steps of prefabricating the positive electrode sheet include:

[0081] Step S1: adding a polyacrylic acid dispersion as a binder into water, and further stirring to form a stable solution system.

[0082] Step S2: Fully mix the positive electrode active material and the conductive carbon, so that the surface of the positive electrode active material is coated with the conductive carbon, thereby achieving the material modification effect and forming a modified powder. The conductive carbon is a mixture of carbon black and graphite. The positive electrode active material is manganese dioxide.

[0083] Step S3: adding the modified powder into the solution system, stirring evenly, and making a positive electrode aqueous slurry.

[0084] Step S4: Coat the positive electrode aqueous slurry on both sides of the current collector with a coating thickness of 0.68-0.71mm. After high-temperature drying, calendering and slitting, the prefabricated positive electrode sheets are formed. The drying temperatures are 90℃, 80℃ and 70℃ respectively. The calendering thickness is 0.43-0.46mm. As shown in the figure, the prefabricated positive electrode sheets at 90℃ and 80℃ are severely cracked, and slightly cracked at 70℃.

[0085] The steps for preparing the pole piece for winding include:

[0086] Step T1: The prefabricated positive electrode sheet treated at a drying temperature of 80° C. in step S4 is heated at the same temperature for a second time to remove moisture and form a lithium battery positive electrode sheet for winding. As shown in the figure, the lithium battery positive electrode sheet cracks during winding.

[0087] Experimental data and description of Examples 1 to 3 and Comparative Examples:

[0088] Table 1: Comparison of coating status of prefabricated positive electrode sheets

[0089]

[0090] As shown in Table 1, adding N-methylpyrrolidone can improve the coating cracking state.

[0091] Table 2: Comparison of winding status of lithium battery positive electrode sheets

[0092]

[0093] It can be seen from Table 2 that, as shown in the figure, the treatment with propylene carbonate makes the positive electrode sheet basically not break during winding.

[0094] Table 3: CR17335 lithium battery discharge performance

[0095]

[0096] It can be seen from Table 3 that after adding propylene carbonate organic solvent, there is basically no difference in the initial discharge performance of the battery and the discharge performance after storage. This is because the electrolyte already contains a certain amount of propylene carbonate, and a slight addition will basically not affect the discharge performance of the battery.

[0097] It should be understood that during the process of softening organic solvent treatment, organic solvent molecules are guided into the interior of the positive electrode, where they fill the tiny gaps left by small molecules such as water, N-methylpyrrolidone (NMP) and binder dispersion after volatilization. These gaps may have weakened the overall structure of the pole piece, but the precise filling of organic solvent molecules not only effectively compensates for these defects, but also plays a bridge-like connecting role, significantly enhancing the flexibility and structural stability of the pole piece during the winding process.

[0098] What is particularly important is that the organic solvents used are not chosen randomly. They are highly compatible with the components in the electrolyte system and are even an indispensable part of the electrolyte. This ensures that even when the organic solvent molecules penetrate into the positive electrode and participate in building a more stable structure, they will not have any adverse effects on the electrochemical performance of the battery. In other words, this innovative method not only optimizes the physical properties of the pole piece, such as improving the resistance to fracture during winding, but also ensures the battery's excellent performance in key electrical performance indicators such as energy density, cycle life, and charge and discharge efficiency.

[0099] In addition, due to the similarity of organic solvents and electrolyte components, their distribution inside the positive electrode complements the natural penetration process of the electrolyte, further promoting the uniform distribution of the electrolyte inside the pole piece, and providing a smoother channel for the rapid transmission of lithium ions. This not only helps to improve the power output capacity of the battery, but also reduces the local overheating or performance degradation problems that may be caused by uneven distribution of the electrolyte, thereby extending the overall service life of the battery.

[0100] In summary, by allowing organic solvent molecules to accurately fill the internal gaps of the positive electrode and ensuring that the electrical performance is not affected, the flexibility and winding stability of the electrode are significantly improved. This innovative strategy has opened up a new path for the research and development of high-performance lithium-ion batteries.

[0101] The technical solution provided by the present invention is introduced in detail above. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the present invention and its core ideas.

[0102] It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility, characterized in that: The method comprises the steps of prefabricating a positive electrode sheet and preparing a winding electrode sheet; The steps of prefabricating the positive electrode sheet include: Step S1: mixing water and N-methylpyrrolidone uniformly, then adding a binder and further stirring to form a solution system; Step S2: fully and evenly mix the positive electrode active material and the conductive carbon to form a modified powder; Step S3: adding the modified powder to the solution system, stirring evenly, and making a positive electrode aqueous slurry; Step S4: coating the positive electrode aqueous slurry on the current collector, drying at high temperature, rolling and cutting to form a prefabricated positive electrode sheet; the steps of preparing the winding electrode sheet include: Step T1: The prefabricated positive electrode sheet is heated at high temperature for a second time to remove moisture; Step T2: applying a softening organic solvent to the prefabricated positive electrode sheet dried in step T1 by liquid spraying or steam infiltration to form a lithium battery positive electrode sheet for the purpose of softening for winding.

2. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: When N-methylpyrrolidone and water are mixed in step S1, the weight proportion of N-methylpyrrolidone is 2-50%.

3. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: The binder used in step S1 includes one or a combination of polyacrylic acid dispersion, polyacrylonitrile dispersion, polytetrafluoroethylene emulsion, and sodium carboxymethyl cellulose aqueous solution.

4. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: The conductive carbon used in step S2 includes one or a combination of two of graphite, carbon black, carbon nanotubes, vapor-grown carbon fibers, graphene, and graphite fluoride.

5. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: In step S4, the positive electrode aqueous slurry is coated on the current collector by transfer or spraying.

6. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: In step S2, the positive electrode active material includes any one of manganese dioxide, iron disulfide, carbon fluoride, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium iron phosphate.

7. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: In step S4, the current collector is copper foil, aluminum foil, or stainless steel foil.

8. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: The softening organic solvent in step T2 includes any one of propylene carbonate, ethylene carbonate, hexanediol dimethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and propylene carbonate.

9. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: In step S4, the positive electrode aqueous slurry is coated on the current collector, and the thickness of the positive electrode sheet including the foil after double-sided coating is 0.50-1.0 mm. The positive electrode sheet formed in step T2 for the purpose of flexibility is formed by rolling the positive electrode sheet in step S4, and the thickness of the positive electrode sheet including the foil after rolling is 0.25-0.50 mm.

10. The method for preparing a thickened positive electrode sheet for a lithium battery for the purpose of increasing flexibility according to claim 1, characterized in that: The weight ratio of the softening organic solvent in step T2 to the prefabricated positive electrode sheet prepared in step T1 is 0.2-10.0%.

Citation Information

Patent Citations

  • Preparation method of high-energy-density lithium iron phosphate battery

    CN118589057A